(untitled) (Journal of Rangpur Medical College, 2026)
Background: Hypothyroidism is the most common thyroid problem in Bangladesh and worldwide. Autoimmune thyroid disease is the most common cause of hypothyroidism. Levothyroxine (LT4) dose requirements vary among patients and may be influenced by thyroid autoantibody status and metabolic comorbidities such as type 2 diabetes mellitus (T2DM) to achieve euthyroidism. Objective: To assess the relationship between thyroid autoantibody status and levothyroxine dose requirements in hypothyroid patients with or without T2DM. Methods: This cross-sectional study was conducted at the Department of Biochemistry, BIRDEM General Hospital, from July 2024 to June 2025 on 100 patients with hypothyroidism recruited from outpatient department of endocrinology, BIRDEM, Dhaka, and divided into two groups: Group 1 (Hypothyroid patients with T2DM, n=50) and Group 2 (Hypothyroid patients without T2DM, n=50). Data on demographic, physical, biochemical variables and dose of levothyroxine were collected. Thyroid peroxidase (TPO) antibody, thyroglobulin (Tg) antibody, TSH and HbA1c were measured. Statistical analysis was performed using SPSS version 29.0. Results: Among 100 patients with hypothyroidism, mean age was 49.66±11.19 years in Group 1 and 45.84±14.4 years in Group 2. TPO antibody positivity was significantly lower in hypothyroid patients with T2DM (36%) compared to those without T2DM (66%) (p=0.003).The mean levothyroxine dose was substantially higher among anti-TPO positive patients than anti-TPO negative patients (67.6±28.0 μg vs. 40.6±17.8 μg, p<0.001), with a similar pattern observed for anti-Tg positivity (74.1±32.3 μg vs. 46.7±20.3 μg, p<0.001). Conclusion: Thyroid autoantibody positivity is strongly associated with higher levothyroxine dose requirements in hypothyroid patients, irrespective of diabetes status. Recognition of thyroid autoimmunity is essential for individualized dose optimization. J Rang Med Col.2026 Mar;11(1):177-182